Dickson voltage multiplier with 1 to 6 stages for dual-band rectifiers (2.45/5.8 GHz) with low input power - Sara El Mattar; Abdennaceur Baghdad; Sara Said; Elhadi Baghaz (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2023)
This paper presents the design of highly efficient rectifiers that can operate at WiFi frequencies (2.45 GHz and 5.8 GHz) and match low input power. The designed dual-band rectifiers use multi-stage dickson voltage multipliers (DVM) (from 1 to 6 stages), and the main idea of this paper is to find the number of stages that offers the best performance and that can be used by applications that operate within the same constraints (operating frequencies, input power). The efficiency and the output voltage (Vout) are the parameters studied to analyze the designed rectifiers. The results showed that as the number of DVM stages increased, the efficiency curves for both frequencies shifted to the higher input power range, even when using the same diode (SMS7630) and the same load (5 KΩ). We concluded that the rectifier with 1-stage DVM is the most suitable to be used for low input power at the selected frequencies since it provides an efficiency of 57.734% at 0 dBm for 2.45 GHz and 36.225% at 1 dBm of input power for 5.8 GHz.